Factors Associated with Postoperative Lipiduria and Hypoxemia in Patients Undergoing Surgery for Orthopedic Fractures - Chen, Chih-Hui; Wu, Yun-Che; Li, Yu-Cheng; Tsai, Feng-An; Li, Jen-Ying; Wang, Jun-Sing; Lee, Cheng-Hung (Frontiers in Surgery, 2022)
We investigated factors associated with postoperative lipiduria and hypoxemia in patients undergoing surgery for orthopedic fractures. We enrolled patients who presented to our emergency department due to traumatic fractures between 2016 and 2017. We collected urine samples within 24 hours after the patients had undergone surgery to determine the presence of lipiduria. Hypoxemia was defined as an SpO2 <95% determined with a pulse oximeter during the hospitalization. Patients’ anthropometric data, medical history, and laboratory test results were collected from the electronic medical record. Logistic regression analyses were used to determine the associations of clinical factors with postoperative lipiduria and hypoxemia with multivariate adjustments. A total of 144 patients were analyzed (mean age 51.3 ± 22.9 years, male 50.7%). Diabetes (odd ratio 3.684, 95% CI 1.256-10.810, p=0.018) and operation time (odd ratio 1.005, 95% CI 1.000-1.009, p=0.029) were independently associated with postoperative lipiduria, while age (odd ratio 1.034, 95% CI 1.003-1.066, p=0.029), body mass index (odd ratio 1.100, 95% CI 1.007-1.203, p=0.035), and operation time (odd ratio 1.005, 95% CI 1.000-1.010, p=0.033) were independently associated with postoperative hypoxemia. We identified several factors independently associated with postoperative lipiduria and hypoxemia in patients with fracture undergoing surgical intervention. Operation time was associated with both postoperative lipiduria and hypoxemia, and we recommend that patients with prolonged operation for fractures should be carefully monitored for clinical signs related to fat embolism syndrome.